Structural characterization of char during co-gasification from torrefied sludge and Yangchangwan bituminous coal - Zhang, Xinsha; Bai, Yonghui; Qin, Jie; Shi, Shengli; Liu, Jiazhong; Wang, Shuaibing; Zhao, Minhui; Shi, Guiming; Ye, Changbing; Yu, Guangsuo (International journal of coal science & technology, 2023)
The present study aims to investigate the physico-chemical structural evolution characteristics of char structure of CO 2 atmosphere torrefaction pretreated sludge with Yangchangwan bituminous coal (YC) during co-gasification. The co-gasification reactivity of torrefied sludge and YC was measured using a thermogravimetric analyzer. The co-gasification reactivity of torrefied sludge with YC was thoroughly explored in depth by in situ heating stage microscope coupled with traditional characterization means of char sample (Scanning electron microscope, nitrogen adsorption analyzer, laser Raman spectroscopy). The results show that the gasification reaction rate of sludge treated under CO 2 atmosphere and coal blended char was better than other char samples at 1100–1200 °C. The torrefied sludge under CO 2 atmosphere promoted its thermal decomposition to the maximum extent, so that it eventually was transformed into a large number of small broken particles. The specific surface area and I D1 /I G ratio of blended char of torrefied sludge under CO 2 atmosphere and YC were 1.70 and 1.07 times higher than that of YC, respectively. The in situ technique revealed that YC char with the addition of torrefied sludge undergo gasification by shrinking core modes and the presence of obvious ash melting flow phenomenon. It was more obvious than that of YC.